The Whole Transcriptome Involved in Denervated Muscle Atrophy Following Peripheral Nerve Injury - Weng, Jian; Zhang, Peixun; Yin, Xiaofeng; Jiang, Baoguo (Frontiers in Molecular Neuroscience, 2018)
Peripheral nerve injury usually leads to progressive muscle atrophy and poor functional recovery. Previous studies have demonstrated that non-coding ribonucleic acid (ncRNA) is a key regulator of muscle atrophy and beneficial for the treatment of peripheral nerve injury. We aimed to analyse the whole transcriptome involved in denervated muscle atrophy after peripheral nerve injury. Animal models of sciatic nerve injury were assessed at 0 (control group), 1, 2, 4, and 8 weeks after injury. The expression patterns in the whole transcriptome in the gastrocnemius muscle were profiled using RNA sequencing at each time point and compared to that obtained in the control group. Six-hundred and sixty-four long non-coding RNAs, 671 microRNAs, 236 circular RNAs, and 12,768 messenger RNAs (mRNAs) were differentially expressed after injury. Changes in some of the differentially expressed ncRNAs and mRNAs were validated using quantitative polymerase chain reaction. Gene Ontology and Kyoko Encyclopedia of Genes and Genomes analysis revealed the potential functions of and relationships among the differentially expressed ncRNAs and mRNAs. To our knowledge, this is the first study to expound the whole transcriptome involved in denervated muscle atrophy, and provides a theoretical basis for further research targeting ncRNAs.